Physical and Aerodynamic Characterization of Particle Clusters at Sakurajima Volcano (Japan) - Gabellini, Pietro; Rossi, Eduardo; Bonadonna, Costanza; Pistolesi, Marco; Bagheri, Gholamhossein; Cioni, Raffaello (Frontiers in Earth Science, 2020)
The process of particle aggregation significantly affects ash settling dynamics associated with volcanic explosive eruptions. Several experiments have been carried out to investigate the physics of ash aggregation and dedicated numerical schemes have been developed to produce more accurate forecasting of ash dispersal and sedimentation. However, numerical description of particle aggregation is complicated by the lack of complete datasets on natural samples required for model validation and calibration. Here we present a first comprehensive dataset for the internal structure, aerodynamical properties (e.g., size, density, terminal velocity) and grain size of constituting particles of a variety of aggregate types collected at Sakurajima Volcano (Japan). Properties were derived based on a combination of High-Resolution-High-Speed videos, Scanning Electron Microscope analysis of aggregates collected on adhesive paper and analysis of tephra samples collected in dedicated trays. Three main types of particle clusters were recognized and quantitively characterised: cored clusters (PC3), coated particles (PC2) and ash clusters (PC1) (in order of abundance). A wide range of terminal velocities (0.5-4 m/s) has been observed for these aggregates, with most values varying between 1 and 2 m/s, while aggregate size varies between 200 and 1200 µm. PC1, PC2 and PC3 have densities between 250-500, 1500-2000 and 500-1500 kg/m3, respectively. The size of the aggregate core, where present, varies between 200 and 750 m and increases with aggregate size. Grain size of tephra samples were deconvoluted into a fine and a coarse Gaussian subpopulation that are well correlated with the grain size of shells and the internal cores of aggregates, respectively. Ash forming the aggregates is always finer than 45 m, confirming the key role played by aggregation processes in fine ash deposition at Sakurajima.